(untitled) (Research, Society and Development, 2022)
The objective was to analyze the epidemiological profile and temporal evolution of hospitalizations, deaths and hospital mortality rate due to sepsis in Brazil between 2017 and 2021. This is an observational, cross-sectional study with a quantitative approach, conducted from the the Hospital Morbidity Information System of the Unified Health System. Data were collected on hospital admissions, deaths and hospital mortality rates for sepsis between 2017 and 2021, according to Brazilian regions, age group, gender, color/race of individuals, and year of care. The results were analyzed using descriptive statistics. A total of 615,805 hospitalizations, 279,765 hospital deaths and a mean hospital mortality rate of 45.49 per 100 hospitalizations per year in Brazil were observed. Both hospitalizations and deaths were more common in the Southeast, among the elderly over 60 years of age, females and caucasians. The mortality rates were higher in the Southeast region, in the age group of 80 years or older, in females and in self-identified blacks. Observing the sex, there was no expressive numerical difference between females and males and regarding color/race, a question mark was raised regarding the completeness of the data. The temporal evolution of hospital admissions and deaths showed an increase until 2019 and reduction until 2021, with hospital mortality rates decreasing until 2019 and increasing until 2021, a result different from those in the literature. Thus, we emphasize the need for further nationwide studies on this grievance, in addition to public policies for early detection of sepsis in this population.